MOLECULAR TYPING OF Giardia duodenalis ISOLATES FROM NONHUMAN PRIMATES HOUSED IN A BRAZILIAN ZOO - David, Erica Boarato; Patti, Mariella; Coradi, Silvana Torossian; Oliveira-Sequeira, Teresa Cristina Goulart; Ribolla, Paulo Eduardo Martins; Guimaraes, Semiramis (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Giardia infections in captive nonhuman primates (NHP) housed at a Brazilian zoo were investigated in order to address their zoonotic potential. Fresh fecal samples were collected from the floors of 22 enclosures where 47 primates of 18 different species were housed. The diagnosis of intestinal parasites after concentration by sedimentation and flotation methods revealed the following parasites and their frequencies: Giardia (18%); Entamoeba spp. (18%); Endolimax nana (4.5%); Iodamoeba spp. (4.5%); Oxyurid (4.5%) and Strongylid (4.5%). Genomic DNA extracted from all samples was processed by PCR methods in order to amplify fragments of gdh and tpi genes of Giardia. Amplicons were obtained from samples of Ateles belzebuth, Alouatta caraya, Alouatta fusca and Alouatta seniculus. Clear sequences were only obtained for the isolates from Ateles belzebuth (BA1), Alouatta fusca (BA2) and Alouatta caraya (BA3). According to the phenetic analyses of these sequences, all were classified as assemblage A. For the tpi gene, all three isolates were grouped into sub-assemblage AII (BA1, BA2 and BA3) whereas for the gdh gene, only BA3 was sub-assemblage AII, and the BA1 and BA2 were sub-assemblage AI. Considering the zoonotic potential of the assemblage A, and that the animals of the present study show no clinical signs of infection, the data obtained here stresses that regular coproparasitological surveys are necessary to implement preventive measures and safeguard the health of the captive animals, of their caretakers and of people visiting the zoological gardens.